Social and Educational Environment of Out-of-school Educational Institutions as a Factor of Social Forming - Литовченко, Олена Віталіївна (Educological discourse, 2014)
In the article some theoretical aspects of the research process of social formation of personality, social and educational environment of out-of-school educational institutions as a factor in this process are presented and discussed.